(untitled) (Actual Problems of Psychology in Educational Institutions, 2021)
The article is devoted to the study of deviant behaviour during adolescence (the theoretical aspect) and the description of the possibilities for resolving this problem with the help of innovative methods. A brief overview of the sources about the causes, the types of deviant behaviour as a stable behaviour of the individual, that deviates from the generally accepted, prevalent, stable social norms, is given. The results of an integrated study of deviant adolescents (the involvement of experts, monitoring, diagnosis) are represented. Innovative forms of work about the prevention of deviant behaviour and its correction: the creation of a bank of convincing evidence in terms of behavioural disorders, «publicity of the act», reinforcement, — are represented